Small Farm Resource Centers as Informal Extension Hubs in Underserved Areas: Case Studies from Southeast Asia - Abram Bicksler; Patrick Trail; Ricky M Bates; Richard R. Burnette; Boonsong Thansrithong (Journal of International Agricultural and Extension Education, 2022)
A Small Farm Resource Center (SFRC) is an informal in-situ extension model used for testing promising agricultural and rural livelihoods options on a physical central site, with some measure of extension methodology. There is a need to evaluate SFRCs as research-extension models operating outside of formal government extension and advisory services. Seven SFRCs located in Southeast Asia were studied to classify extension methodologies adopted by those centers, evaluate extension efficacy, and to provide recommendations for amplifying their services. On average in 2013, SFRCs were 21.1 years old, covered 24.2 ha, cost 242,000 USD to establish and had a yearly operating cost of 28,500 USD. The work of the seven SFRCs could be classified into five predominant extension methodologies: on-site and off-site demonstrations, on-site and off-site trainings, and off-site extension outreach. Most of the SFRCs utilized combinations of these and tailored their methods to the particular context. Besides agricultural production, SFRCs also offered socio-cultural and socio-economic assistance, owing to a cycle of extension knowledge refinement. SFRCS were re-engaged in 2021 and all 7 were still operational, and the majority provided the same number or more services (57%) as in 2013, utilized the same amount of space (71%), and were perceived to have the same or more efficacy (71%) even in the face of decreasing or stagnating funding (71%) due to the COVID-19 pandemic. Overall, SFRCs continue to be used successfully throughout Southeast Asia and provide cost-effective and needs-based extension and advisory services to underserved populations outside of formal extension services.
Keywords: agricultural extension methods; needs-based assessment; rural advisory services; Southeast Asia; demonstration plots; learning center